PAKHTOONKHAWA, PAKISTAN - F. U. Rahman; F. Perveen; T. Rauf; M. Salim; S. Khan; H. Ullah; A. Ullah; Z. Kamal; Z. Ali (Journal of Animal and Plant Sciences, 2015)
The present study was conducted to explore the bats of Khyber Pakhtunkhwa, Pakistan. During the present study 52 bats were collected through the mist nets from FR, Peshawar in District Peshawar and Mazdurabad and Ghanu Deri from District Mardan for a period of two years from July 2011 to May 2013. They were identified on the basis of morphological and cranial measurements. Mean (±SD) of the body mass (BM), head and body length (HBL), forearm length (FA) and wingspan (WS) were identified as 19.09±1.36 mm, 65.29±2.20 mm, 68.71±1.05 mm and 197±9.7 mm, respectively. The tail is shorter than the forearm proportionally. While the skull is sagittal and measured ascondylo- canine length (CCL) 18.61±0.21 mm, greater skull length (GTL) 19.64±0.21 mm and Zygomatic breadth (ZB)12.13±0.15 mm. There were no significant (P<0.05) morphological and cranial variations among all the samples collected from the study area. On the basis of morphological and cranial measurements the species was identified as R. microphyllum for the first time and after 27 years from the Khyber Pakhtunkhwa. and light and accumulate fat during the autumn and
Keywords: Chiroptera; morphology; Charsadda; greater Asiatic yellow bat; Pakistan.